Produção de cistos e biomassa de “branchoneta” Dendrocephalus brasiliensis, Pesta 1921, em viveiros de cultivo - LOPES, José Patrocínio (2002)
The objective of this work was to develop a methodology for the production of cysts and biomass of Dendrocephalus brasiliensis, at Paulo Afonso Fisheries Station (09º22'38 "S and 38º13'58" W), Paulo Afonso, BA, Brazil. The purpose of making possible the use of the branchoneta as an alternative food source for fish and crustaceans. The research consisted of two treatments (inoculation and without inoculation of D. brasiliensis cysts) blocked in time (May and October), with two replicates for each treatment / block combination. For this, four semi-excavated nurseries of 2,000 m2 each were used. Two nurseries were inoculated with 2g of cysts and the other two nurseries were not inoculated and only hatching of nauplii occurred due to the natural production of this microcrustacean previously existing in these nurseries. After 15 days of cultivation, the treatment with inoculation produced 20.75 ± 2.31 g of cysts, being higher than that without inoculation, which produced only 7.75 ± 2.31 g, thus occurring a significant difference (P < 0.05) according to the analysis of variance and the mean comparison test (Tukey at 5%). In this way, an average of 2.075g / ha / year of cysts was produced. Regarding the biomass production, the statistical analysis showed that the average obtained with inoculation of 2 g of cysts per nursery, of 18.63 ± 0.74 kg was superior to 8.00 ± 0.75 kg of the treatment without inoculation. Thus it is possible to produce a biomass of 1,863 kg / ha / year.